Preparation method of perovskite battery with polymer self-assembled single-layer film
By optimizing the solvent system and process technology, a self-assembled single-layer film of Poly-4PACz polymer is uniformly coated on a large-area substrate, solving the problem of insufficient film thickness and uniformity in perovskite solar cells, significantly improving the photoelectric performance and stability, and providing technical support for industrial production.
Patent Information
- Application Number
- CN202510316980.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-17
AI Technical Summary
A uniform coating and efficient film formation of polymer self-assembled single-layer films in perovskite solar cells are achieved on a large-area substrate. Especially when the substrate surface roughness is large, the film layer thickness and uniformity are limited, and the multi-layer stacking effect of small molecule SAM increases interface resistance and reduces the device's photoelectric performance.
By optimizing the solvent system, using a mixed solvent of ethanol and dimethyl sulfoxide, combined with slit coating process and vacuum film formation technology, uniform coating of Poly-4PACz polymer self-assembled single layer film is achieved on a large-area substrate.
The uniform coating of a single layer film is achieved at a high-speed coating rate of 20mm/s on a large-area substrate, which significantly improves the film-forming characteristics of the perovskite film, improves the photoelectric performance and long-term stability of the components, and provides a potential technical route for the industrial production of perovskite solar cell modules.
Smart Images

Figure CN119855353A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a perovskite solar cell having a polymer self-assembled monolayer film, and relates to the technical field of perovskite solar cells. Background Art
[0002] Perovskite solar cells are regarded as the core representative of the next generation of photovoltaic technology due to their high photoelectric conversion efficiency, low-cost preparation process and good scalability. In particular, pin-type (inverted structure) perovskite solar cells have shown great potential in commercial applications due to their low-temperature processing, excellent interface stability and adaptability to large-area preparation. However, how to achieve uniform coating on large-area substrates is still the main technical challenge currently faced.
[0003] Hole transport materials play a key role in perovskite solar cells, and their quality directly affects the uniformity of the film and the final performance of the device. Traditional polytriarylamine (PTAA) hole transport materials are widely used due to their good hole extraction ability and chemical stability, but their hydrophobicity leads to insufficient coating uniformity on large-area substrates, limiting the improvement of device performance. To solve these problems, small molecule self-assembled monolayers (SAMs) based on carbazole phosphate (PACz) have been developed in recent years. These SAM materials form chemical bonds with the surface of transparent conductive oxides (TCOs) through their phosphate groups, showing good effects in interface passivation and hole extraction. However, the following problems of SAM materials in large-area coating still need to be solved: the thickness and uniformity of the film layer are limited, especially when the surface roughness of the substrate is large, incomplete coverage is prone to occur; the multilayer stacking effect of small molecule SAM increases the interface resistance, thereby reducing the optoelectronic performance of the device, and the photothermal stability is limited; in large-scale processes such as blade coating or slit coating, the film quality is easily affected by environmental conditions (such as humidity and temperature).
[0004] To solve the above problems, researchers developed a polymer hole transport material Poly-4PACz. Poly-4PACz is prepared by polymerizing carbazole phosphate monomers. This method achieves uniform film formation in small-area experiments and exhibits efficient hole extraction capabilities and interface passivation effects. However, Poly-4PACz still has the above problems in large-area preparation, and there are currently no related reports. Summary of the invention
[0005] In view of this, the present application provides a method for preparing a perovskite cell with a polymer self-assembled monolayer film, which achieves uniform coating of a monolayer film on a large-area substrate by optimizing the solvent system, adopting a slit coating process, and introducing vacuum film forming technology.
[0006] According to one aspect of the present application, a method for preparing a perovskite cell with a polymer self-assembled monolayer film is provided, wherein the perovskite cell with a polymer self-assembled monolayer film is suitable for being arranged on an external substrate, and comprises the following steps: step one: depositing a transparent conductive substrate on the substrate, and then preparing a hole transport layer on the conductive substrate; step two: forming a polymer self-assembled monolayer on the hole transport layer, and the solute of the precursor solution of the polymer self-assembled monolayer is Poly-4PACz, and the solvent comprises ethanol and dimethyl sulfoxide; step three: coating a perovskite precursor material on the polymer self-assembled monolayer to form a perovskite light absorption layer; step four: depositing an electron transport material on the perovskite light absorption layer to form an electron transport layer; step five: depositing a back electrode on the electron transport layer.
[0007] According to one aspect of the present application, Poly-4PACz is dissolved in a mixed solvent of ethanol and dimethyl sulfoxide by magnetic stirring to form a polymer solution.
[0008] According to one aspect of the present application, the volume ratio of ethanol to dimethyl sulfoxide is 0.5:1 or 0.8: or 1:1 or 1.5:1.
[0009] According to one aspect of the present application, the polymer solution is deposited on the hole transport layer by slit coating, vacuum film forming is performed for 40 seconds, and annealing is performed at 100° C. for 10 minutes to form a polymer self-assembled monolayer film.
[0010] According to one aspect of the present application, the speed of the slot coating is 20 mm / s.
[0011] According to one aspect of the present application, the substrate is a glass substrate, and one of an indium tin oxide film and a fluorine-doped tin oxide film is deposited on the glass substrate to form a transparent conductive substrate; a nickel oxide film is deposited on the conductive substrate by spin coating or magnetron sputtering to form a hole transport layer.
[0012] According to one aspect of the present application, the precursor solution of the perovskite light absorption layer is a solution of AX and BX2, and the solvent of the perovskite precursor solution is dimethylamide and dimethyl sulfoxide; wherein the A position is composed of any cation of cesium, rubidium, potassium, amine, amidine or alkali family; the B position is composed of any divalent metal cation of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium; the X position is composed of any anion of chlorine, bromine, iodine, thiocyanate, cyanide, oxycyanide, acetate, azide, and borohydride.
[0013] According to one aspect of the present application, a fullerene layer is deposited on the perovskite light absorbing layer by thermal evaporation or spin coating to form an electron transport layer; and a bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form a hole blocking layer.
[0014] According to one aspect of the present application, a metal electrode is deposited on the hole blocking layer to form a back electrode, and the material of the back electrode is silver or copper.
[0015] According to one aspect of the present application, the chemical structure of Poly-4PACz is: .
[0016] The beneficial effects of the present invention are as follows: due to the ethanol / dimethyl sulfoxide solvent system, the solubility and film-forming properties of Poly-4PACz are significantly improved, and a single-layer film is uniformly coated on a large-area substrate at a high-speed coating rate of 20 mm / s, providing an ideal interface for the subsequent solution deposition of the perovskite light absorption layer, significantly improving the film-forming properties of the perovskite film and passivating defects, improving the photoelectric performance and long-term stability of the component, and providing a potential technical route for the industrial production of perovskite solar cell components. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The structure diagram of the perovskite battery of the method for preparing the perovskite battery with a polymer self-assembled monolayer film of this embodiment; Figure 2 The chemical structure diagram of Poly-4PACz; Figure 3 It is an atomic force microscope comparison diagram of comparative example 1, embodiment 1 and embodiment 4; Figure 4 Atomic force microscope comparison diagram of Example 1, Example 2, Example 3, Example 4 and Example 5; Figure 5 This is a scanning electron microscope comparison image of the perovskite of Comparative Example 1; Figure 6 This is a scanning electron microscope comparison image of the perovskite of Example 1; Figure 7 This is a scanning electron microscope comparison image of the perovskite of Example 2; Figure 8 This is a scanning electron microscope comparison image of the perovskite of Example 3; Fig. 9 This is a scanning electron microscope comparison image of the perovskite of Example 4; Fig.10 This is a scanning electron microscope comparison of the perovskite of Example 5 Fig.11 The efficiency curve of the perovskite cell with a polymer self-assembled monolayer film; Fig.12 This is a vacuum film forming diagram of Example 4. DETAILED DESCRIPTION
[0018] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0019] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0020] The present application provides a method for preparing a perovskite cell with a polymer self-assembled monolayer film, wherein the perovskite cell with a polymer self-assembled monolayer film is suitable for being arranged on an external substrate, and comprises the following steps: step one: depositing a transparent conductive substrate ① on the substrate, and then preparing a hole transport layer on the conductive substrate ①; step two: forming a polymer self-assembled monolayer ③ on the hole transport layer ②, and the solute of the precursor solution of the polymer self-assembled monolayer ③ is Poly-4PACz, and the solvent includes ethanol and dimethyl sulfoxide; step three: coating a perovskite precursor material on the polymer self-assembled monolayer ③ to form a perovskite light absorption layer ④; step four: depositing an electron transport material on the perovskite light absorption layer ④ to form an electron transport layer ⑤; step five: depositing a back electrode ⑦ on the electron transport layer ⑤.
[0021] like Figure 1 As shown, the substrate serves as the supporting structure of the perovskite cell, and a transparent conductive substrate ① is deposited thereon, which is used as an electrode material for subsequent charge collection and transport. A hole transport layer ② is prepared on the transparent conductive substrate ① to help holes be effectively transported from the perovskite layer to the electrode. Then, a polymer-type hole transport material Poly-4PACz is prepared on the hole transport layer ② to effectively passivate the interface and form a polymer self-assembled monolayer ③. The perovskite precursor material is coated on the polymer self-assembled monolayer ③ to form a perovskite light absorption layer ④. An electron transport material is deposited on the perovskite light absorption layer ④ to form an electron transport layer ⑤ to help electrons be transported from the perovskite layer to the electrode layer, and then a hole blocking layer ⑥ is prepared on the electron transport layer ⑤ to protect the perovskite light absorption layer ④ and the electron transport layer ⑤ and promote the efficiency of charge collection. Finally, the back electrode⑦ is deposited as the top electrode of the entire solar cell, and the prepared perovskite photovoltaic cell is packaged and tested. The packaging can prevent the impact of environmental conditions on device performance, such as changes in light and humidity. The performance of the packaged perovskite solar cell needs to be tested, including the photoelectric conversion efficiency (PCE), short-circuit current density (Jsc), open circuit voltage (Voc) and fill factor (FF) to evaluate the photoelectric conversion efficiency and stability during the process.
[0022] According to one aspect of the present application, Poly-4PAC is dissolved in a mixed solvent of ethanol and dimethyl sulfoxide by magnetic stirring to form a polymer solution.
[0023] like Figure 2 As shown, in one achievable manner, a solute Poly-4PACz is selected in a precursor solution of a polymer self-assembled monolayer ③, and the solvent includes EtOH (ethanol) and DMSO (dimethyl sulfoxide).
[0024] According to one aspect of the present application, the volume ratio of ethanol to dimethyl sulfoxide is 0.5:1, 0.8:1, 1:1, 1.5:1.
[0025] According to one aspect of the present application, the polymer solution is deposited on the hole transport layer ② by slit coating, vacuum film forming is performed for 40 seconds, and annealing is performed at 100° C. for 10 minutes to form a polymer self-assembled monolayer film.
[0026] Preferably, coating the polymer self-assembled monolayer ③ on the hole transport layer ② further comprises: depositing a polymer hole transport material Poly-4PACz precursor solution on the NiOx layer by slit coating, performing vacuum film forming for 40 seconds, and annealing at 100° C. for 10 minutes.
[0027] Preferably, the slit coating speed is 20 mm / s.
[0028] According to one aspect of the present application, the substrate is a glass substrate, and one of an indium tin oxide thin film and a fluorine-doped tin oxide thin film is deposited on the glass substrate to form a transparent conductive substrate ①; a nickel oxide thin film is deposited on the conductive substrate ① by spin coating or magnetron sputtering to form a hole transport layer ②.
[0029] Depositing a conductive substrate ① on a substrate also includes: the substrate is a glass substrate, and an ITO (indium tin oxide) or FTO (fluorine-doped tin oxide) film is deposited on the glass substrate to form a transparent conductive oxide (TCO) coating; preparing a hole transport layer ② on TCO also includes: depositing a NiOx (nickel oxide) film on the conductive substrate ① by spin coating or magnetron sputtering.
[0030] According to one aspect of the present application, the precursor solution of the perovskite light absorption layer ④ is a solution of AX and BX2, and the solvent of the perovskite precursor solution is dimethylamide and dimethyl sulfoxide; wherein the A position is composed of any cation of cesium, rubidium, potassium, amine, amidine or alkali family; the B position is composed of any divalent metal cation of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium; the X position is composed of any anion of chlorine, bromine, iodine, thiocyanate, cyanide, oxycyanide, acetate, azide, and borohydride.
[0031] Preferably, in an achievable manner, preparing the perovskite precursor solution further comprises: preparing a solution containing perovskite precursor substances AX and BX2, and the solvent of the perovskite precursor solution is DMF and DMSO.
[0032] In one feasible manner, the A position is composed of any cation of cesium, rubidium, potassium, amine, amidine or alkali family; the B position is composed of any divalent metal cation of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth and polonium; the R position is composed of any of phenylethylamine, 1,4-butanediamine and guanidine; the X position is composed of any anion of chlorine, bromine, iodine, thiocyanate, cyanide, oxycyanate, acetate, azide and borohydride; and the solvent is DMF (dimethylformamide) and DMSO (dimethyl sulfoxide).
[0033] In this embodiment, when preparing the perovskite precursor solution, the perovskite precursor solution contains AX and BX2 substances. The perovskite structure is ABX3, wherein A is any cation of cesium, rubidium, potassium, amine, amidine or alkali family, B is any divalent metal cation of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium, and X is any anion of chlorine, bromine, iodine, thiocyanate, cyanide, oxycyanide, acetate, azide, and borohydride.
[0034] According to one aspect of the present application, a fullerene layer is deposited on the perovskite light absorption layer ④ by thermal evaporation or spin coating to form an electron transport layer; a bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form a hole blocking layer ⑥; a metal electrode is deposited on the hole blocking layer ⑥ to form a back electrode, and the material of the back electrode is silver or copper.
[0035] Preparing a hole blocking layer ⑥ on the electron transport layer ⑤ also includes: depositing a bath copper layer (BCP) on the electron transport layer ⑤ by thermal evaporation or spin coating to protect the perovskite layer and the electron transport layer ⑤ and promote charge collection efficiency. Preparing a back electrode ⑦ on the hole blocking layer ⑥ and encapsulating the perovskite solar cell also includes: depositing a metal electrode on the hole blocking layer ⑥ to complete the preparation of the perovskite solar cell, encapsulating the prepared solar cell, and performing performance testing on the encapsulated perovskite solar cell.
[0036] In one achievable manner, preparing the electron transport layer ⑤ on the perovskite light absorption layer ④ also includes: depositing a fullerene (C60 or PCBM) layer on the perovskite light absorption layer ④ by thermal evaporation or spin coating, which is used as an electron transport material to help electrons be transported from the perovskite layer to the electrode layer.
[0037] Preferably, coating the perovskite precursor solution on the polymer self-assembled monolayer ③ further comprises: depositing the perovskite precursor solution on the SAM layer by slit coating, and annealing at 150° C. for 10 minutes.
[0038] In this embodiment, a metal electrode is deposited on the BCP layer as the top electrode of the entire perovskite solar cell, wherein the metal electrode is silver or copper. The completed perovskite solar cell device is packaged to prevent the environmental conditions from affecting the device performance, and is subjected to performance tests, including testing the photoelectric conversion efficiency (PCE), short-circuit current density (Jsc), open circuit voltage (Voc) and fill factor (FF) to evaluate the photoelectric conversion efficiency and stability of the device.
[0039] The present invention dissolves Poly-4PACz in an optimized solvent system of EtOH (ethanol) / DMSO (dimethyl sulfoxide), configures a mixed solvent with a volume ratio of ethanol / dimethyl sulfoxide of 0.5:1, 0.8:1, 1:1, and 1.5:1, and fully dissolves it by magnetic stirring. The optimization of the solvent ratio is mainly based on the synergistic effect of surface energy regulation and dissolution kinetics balance. Although the DMSO-rich system has a high dissolution efficiency, the excessive solvent residue causes a coffee ring effect in the film-forming process, and the EtOH-rich system has insufficient dissolution capacity, resulting in a decrease in solution stability. Experiments have found that when the EtOH / DMSO volume ratio is 1:1, the system exhibits the best synergistic dissolution characteristics: the high polarity of DMSO effectively destroys the π-π stacking effect between polymer chains, and the moderate volatility of ethanol is conducive to the gradient volatilization process of the solvent in the subsequent coating process. This balance enables the polymer molecules to achieve orderly self-assembly on the substrate surface to form a dense and uniform monolayer structure.
[0040] The prepared SAM solution can be evenly coated on the surface of the prepared hole transport layer ② through the slit coating technology. The kinetic parameters and post-processing conditions of the slit coating method have a decisive influence on the quality of the film. This study systematically regulates the coating speed (8-30 mm / s) and the thermal annealing temperature (80-120℃), and the distance between the meniscus and the substrate is 120 μm, revealing the relationship between process parameters and film morphology, molecular orientation and device performance. In terms of coating speed optimization, the study found that when the coating speed is lower than 15 mm / s, the solution stays on the substrate surface for too long, and the difference in solvent evaporation gradient leads to excessive molecular aggregation; when the speed exceeds 25 mm / s, the shear force-induced molecular orientation is mismatched with the solvent evaporation rate, resulting in an increase in the density of pinhole defects. The preferred coating speed of 20 mm / s can balance the shear force field action time and the solvent evaporation kinetics. Using the optimized solvent system in the present invention, the repeatability and stability of film formation in the large-area coating process are achieved at a high-speed coating rate of 20 mm / s. Subsequently, vacuum film forming technology was used for auxiliary treatment for 40 seconds to quickly remove high-boiling point solvent residues such as DMSO and inhibit the formation of coffee rings. Thermal annealing was then performed. Due to the high sensitivity of polymers to temperature, in order to avoid structural damage, the treatment temperature was preferably 100°C and the treatment time was 10 minutes. A highly uniform self-assembled polymer monolayer film with excellent hole extraction and interface passivation capabilities was prepared.
[0041] In order to illustrate the superiority of the highly uniform polymer self-assembled monolayer film of the present application, the following examples are now carried out: Embodiment 1, embodiment 2 and embodiment 3 are all prepared by the same process method as the technical solution of the present application. Preferably, the TCO anode here adopts ITO, the perovskite A position adopts CsFAMA ternary cation mixed component, the B position is Pb, the X position is I and Br mixed component, Poly-4PACz is dissolved in EtOH (ethanol) / DMSO (dimethyl sulfoxide) mixed solvent, the solvent volume ratio is adjustable, the electron transport layer ⑤ adopts PCBM (fullerene derivative), and the back electrode ⑦ adopts Ag.
[0042] Comparative Example 1 Comparative Example 1 is a single dimethyl sulfoxide without a SAM layer. In Comparative Example 1, a perovskite precursor solution is directly deposited on the hole transport layer ② without a polymer self-assembled monolayer film, and the rest of the preparation process is not modified.
[0043] Comparative Example 2 Comparative Example 1 is a single dimethyl sulfoxide with a SAM layer. In Comparative Example 2, a polymer self-assembled monolayer is prepared on the hole transport layer ② and subjected to thermal annealing treatment. The treatment temperature is preferably 100° C. and the treatment time is 10 min. The rest of the preparation process is not modified.
[0044] Example 1 The ratio of ethanol to dimethyl sulfoxide in the mixed solvent of Example 1 is 1:1, and there is a SAM layer.
[0045] Compared with Comparative Example 1 and Comparative Example 2, in Example 1, a polymer self-assembled monolayer film is prepared on the hole transport layer ② and subjected to thermal annealing treatment. The treatment temperature is preferably 100° C. and the treatment time is 10 min. The other preparation processes are not modified.
[0046] Example 2 The ratio of ethanol to dimethyl sulfoxide in the mixed solvent of Example 2 is 0.5:1, and there is a SAM layer. In Example 2, a polymer self-assembled monolayer film is prepared on the hole transport layer ②, and a vacuum film forming treatment is first performed for 40 seconds, and then a thermal annealing treatment is performed. The treatment temperature is preferably 100°C and the treatment time is 10 minutes. The other preparation processes are not modified.
[0047] Example 3 The ratio of ethanol to dimethyl sulfoxide in the mixed solvent of Example 3 is 0.8:1, and there is a SAM layer. The remaining steps and conditions are the same as those of Example 2.
[0048] Example 4 The ratio of ethanol to dimethyl sulfoxide in the mixed solvent of Example 4 is 1:1, and there is a SAM layer. The remaining steps and conditions are the same as those of Example 2.
[0049] Example 5 The ratio of ethanol to dimethyl sulfoxide in the mixed solvent of Example 5 is 1.5:1, and there is a SAM layer. The remaining steps and conditions are the same as those of Example 2.
[0050] according to Figure 3-Figure 4 The AFM images of Example 1, Example 2 and Example 3 show that, compared with the single DMSO solvent, the coating thickness uniformity of the mixed solvent system on a 100 cm² substrate is significantly improved, and the surface roughness of the film layer is reduced from 30 nm to 10 nm (10 nm for Example 4 and 22 nm for Comparative Example 2). In addition, in the ethanol / dimethyl sulfoxide solvent system, after vacuum film formation, the coverage uniformity of the edge area is significantly improved compared with traditional thermal annealing.
[0051] The typical photoelectric conversion efficiency of Example 1 is 13.8%. The open circuit voltage and short circuit current of Examples 2 and 3 are higher than those of Example 1, and their photoelectric conversion efficiencies are 15.1% and 16.5%, respectively, which are significantly improved. Figure 6 The test conditions are AM1.5G, 100mW / cm 2 .
[0052] Figure 7It shows that the current of Example 3 remains stable within 500 seconds.
[0053] The above-mentioned Examples 1, 2 and 3 were placed under an LED light source to perform a JV curve test. The Example 3 with the highest efficiency in the present invention had an open circuit voltage of 1.0 V and a short circuit current density of 22.62 mA / cm 2 , the fill factor is 73%, the photoelectric conversion efficiency is 16.5%, the open circuit voltage of Example 2 is 0.985 V, and the short circuit current density is 22.05 mA / cm 2 , the fill factor is 69%, the photoelectric conversion efficiency is 15.1%, while the open circuit voltage of Example 1 is 0.923 V and the short circuit current density is 22.27 mA / cm 2 , the fill factor is 67%, and the photoelectric conversion efficiency is 13.8%, as shown in Table 1.
[0054] Table 1: It should be noted that although the present application is used as an example to introduce a perovskite solar cell with a directional interface perovskite light absorption layer as above, those skilled in the art will understand that the present application should not be limited thereto. In fact, the user can flexibly set various parameters according to personal preferences and / or actual application scenarios, as long as the design is reasonable.
[0055] Through the technical means of the present invention, due to the innovative ethanol / dimethyl sulfoxide green solvent system, the solubility and film-forming properties of the polymer hole transport layer ② material Poly-4PACz are significantly improved, and a single-layer film is uniformly coated on a large-area substrate at a high-speed coating rate of 20 mm / s, which provides an ideal interface for the subsequent solution deposition of the perovskite light absorption layer, significantly improves the film-forming properties of the perovskite film and passivates defects, enhances the photoelectric performance and long-term stability of the component, and provides a potential technical route for the industrial production of perovskite solar cell components.
[0056] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a perovskite cell having a polymer self-assembled monolayer film, wherein the perovskite cell having a polymer self-assembled monolayer film is suitable for being arranged on an external substrate, characterized in that: The following steps are involved: Step 1: depositing a transparent conductive substrate on a substrate, and then preparing a hole transport layer on the conductive substrate; Step 2: forming a polymer self-assembled monolayer on the hole transport layer, wherein the solute of the precursor solution of the polymer self-assembled monolayer is Poly-4PACz, and the solvent includes ethanol and dimethyl sulfoxide; Step 3: coating the perovskite precursor material on the polymer self-assembled monolayer to form a perovskite light absorption layer; Step 4: depositing an electron transport material on the perovskite light absorption layer to form an electron transport layer; Step 5: depositing a back electrode on the electron transport layer; The volume ratio of the ethanol to dimethyl sulfoxide is 0.5:1 or 0.8:1 or 1:1 or 1.5:
1.
2. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 1, characterized in that: Poly-4PAC was dissolved in a mixed solvent of ethanol and dimethyl sulfoxide by magnetic stirring to form a polymer solution.
3. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 2, characterized in that: The polymer solution was deposited on the hole transport layer by slit coating, vacuum film forming was performed for 40 seconds, and annealing was performed at 100° C. for 10 minutes to form a polymer self-assembled monolayer film.
4. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 3, characterized in that: The speed of the slot coating was 20 mm / s.
5. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 4, characterized in that: The substrate is a glass substrate, and one of an indium tin oxide film and a fluorine-doped tin oxide film is deposited on the glass substrate to form a transparent conductive substrate; A nickel oxide film is deposited on a conductive substrate by spin coating or magnetron sputtering to form a hole transport layer.
6. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 5, characterized in that: The precursor solution of the perovskite light absorption layer is a solution of AX and BX2, and the solvent of the perovskite precursor solution is dimethylamide and dimethyl sulfoxide; Wherein, the A position is composed of cesium, rubidium, potassium, amine, amidine or any cation in the base family; The B position is composed of any divalent metal cation selected from the group consisting of lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium; The X position is composed of any anion selected from the group consisting of chlorine, bromine, iodine, thiocyanate, cyanide, oxycyanate, acetate, azide, and borohydride.
7. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 6, characterized in that: Depositing a fullerene layer on the perovskite light absorbing layer by thermal evaporation or spin coating to form an electron transport layer; A bath copper layer is deposited on the electron transport layer by thermal evaporation or spin coating to form a hole blocking layer.
8. The method for preparing a perovskite battery having a polymer self-assembled monolayer according to claim 7, characterized in that: A metal electrode is deposited on the hole blocking layer to form a back electrode, and the material of the back electrode is silver or copper.
9. The method for preparing a perovskite battery having a polymer self-assembled monolayer film according to claim 8, characterized in that: The chemical structure of Poly-4PACz is: 。
Citation Information
Patent Citations
Polyphosphocarbazole material, preparation method and application in photoelectric device
CN117050277A
Preparation method and application of self-assembled monomolecular layer, perovskite solar cell and preparation method of perovskite solar cell
CN117998941A
Polycyclic phosphoric acid polymer material as well as preparation method and application thereof
CN118307750A
Perovskite devices
WO2025023894A1